Psychological Disorders in the World of Education: Examining the Relationship between Behavioral Disorders and Learning Disorders on Mental Health - Majid, Asmarani (International Journal on Advanced Science, Education, and Religion, 2024)
The world of education is not free from various challenges, one of which is psychological disorders that can have an impact on the academic development and mental well-being of students. Behavioral disorders and learning disorders are two aspects that are often found in educational environments and have a complex relationship with mental health. Behavioral disorders such as ADHD, oppositional defiant disorder (ODD), and social anxiety disorder can affect students' social interactions and discipline at school. Meanwhile, learning disorders such as dyslexia, dysgraphia, and dyscalculia are often obstacles to academic achievement, which in turn can increase the risk of stress and low self-confidence in students. This study aims to examine the relationship between behavioral disorders and learning disorders with mental health in the world of education. The method used is a qualitative approach with literature studies and empirical analysis of various related studies. The results of the study show that behavioral disorders and learning disorders not only affect academic achievement, but also the psychological condition of students, including the emergence of anxiety, depression, and feelings of helplessness. Therefore, a comprehensive approach is needed from various parties, including educators, psychologists, and parents, to create a supportive learning environment and effective intervention strategies to minimize the negative impact of psychological disorders in the world of education.